Protective effect of whey cheese matrix on probiotic strains exposed to simulated gastrointestinal conditions - Madureira, A. Raquel; Amorim, Manuela; Gomes, Ana M.; Pintado, Manuela E.; Malcata, F. Xavier (Food research international, 2011)
A probiotic whey cheese added with Lactobacillus casei LAFTI®L26, Lactobacillus acidophilus LAFTI®L10 or Bifidobacterium animalis Bo was subject in vitro to sequential conditions that parallel the four major steps of digestion: mouth (artificial saliva), oesophagus–stomach (artificial gastric juice), duodenum (artificial intestinal juice) and ileum; its manufacture followed the traditional cheesemaking protocol of Portuguese Requeijão. MRS broth was inoculated in parallel as reference medium, to ascertain the protective effect of the whey cheese matrix itself upon those strains in every digestion step. Mouth conditions had an almost negligible effect upon all three strains, whereas oesophagus–stomach, duodenum and ileum conditions decreased the viable numbers of L. casei and L. acidophilus; in both systems, B. animalis suffered only slight decreases in viable numbers; and L. casei and L. acidophilus behaved likewise in MRS exposed to duodenum and ileum conditions. Whey cheese matrices thus appeared to protect the aforementioned three strains during transit throughout the simulated gastrointestinal system, so they are promising carriers of those probiotic bacteria.